Perancangan Sistem Informasi Point Of Sale dan Pencatatan Akuntansi Penjualan Kavling Tanah Berbasis Website - Thommy Willay (Jurnal Esensi Infokom : Jurnal Esensi Sistem Informasi dan Sistem Komputer, 2025)
In the era of globalization and technology today, computer technology has become one of the most essential technologies in every aspect of human life. Mitra Sejahtera is one of the companies operating in the field of land sales in Pontianak. In the process of recording sales, it is still manually, which means transactions are recorded in a book as a record of sales or transactions. The transaction receipts that are issued are still manually, which causes issues during operations. A common issue is when sales are made, buyers experience long waits as the cashier records the sales, leading to a buildup of customers waiting during the transaction process, whether paid in cash or make a installments. The same thing happens in the company's accounting records, where errors often occur due to discrepancies between the accounting records and the transactions carried out. In system development using the waterfall method, object-oriented system analysis is conducted with UML modeling. Website development utilizes programming languages HTML, CSS, and PHP, along with a MySQL database. The result is that the point of sale information system with integrated accounting recording is designed to address the time required for transaction recording, namely by using a sales receipt printing system and directly scanning the accounting recording process. This aims to expedite the company's operational processes and reduce the likelihood of errors in transaction recording